Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of loss in mass of crude sodium borates after heating at a temperature of 900°C Part 9, (28th February 1979) - British Standards Institution,
No abstract available